A eugenia na obra de Renato Kehl após 1945 e sua relação com a psicologia e a educação no Brasil - Faggion, Melline Ortega (2024)
The outcome of World War II influenced the trajectory of eugenic ideas, including attempts to forget and characterize eugenics as pseudoscience. The historical context that contributed to modifying the discourse on the improvement of the “race”, coincided with the phase of consolidation of psychology as a science in Brazil. This fact allows questioning whether there was a relationship between psychology and eugenics from 1945 onwards. Based on this question, bibliographic research inspired by the principles of historical-dialectical materialism was conducted. Four works by Renato Ferraz Kehl, one of the main exponents of eugenics in Brazil, were selected for this research. The objective of this study was to investigate Kehl’s productions from 1945 onwards, seeking to verify how psychological knowledge was integrated into his works and whether these presented a eugenic character. A survey of Kehl’s productions indicated eight works in the period adopted for this study; the selection criterion was the materials that approached psychology and philosophy, an area historically fundamental to the development of scientific psychology. The selected works were: Guia sinóptico de filosofia – notas de estudos (1945), Através da Filosofia (1946), A interpretação do homem (1951), and Filosofia e Bio-perspectivismo (1955). From the analysis of these works, it was observed that Renato Kehl did not abandon the defense of the improvement of the “race”, as he continued to discuss eugenics. For this purpose, the psychological knowledge in vogue at the time, as well as knowledge from Philosophy, served his project of defending eugenics and allowed him to present his eugenic premises with a different rhetoric from the explicit eugenic discourse of the early 20th century. Education also appeared in his writings, serving as an instance for constitution of eugenics conscience and to mitigate the manifestation of hereditary characteristics in individuals. It was concluded that Kehl’s eugenic thought persisted with an expression articulated to the field of characterology, the interpretation of Man, and the debate on the historical trajectory and function of Philosophy. The appropriation of psychological knowledge occurred due to the author’s identification with elements that integrate the project of scientific psychology, such as the possibility of investigating human characteristics. It is hoped that this research can shed light on a relevant topic in the field of the History of Psychology: when theories and initiatives are carried out in favor of a project for Psychology and when there is a project for which psychological knowledge can serve